2018
DOI: 10.3389/fneur.2018.00468
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging (DTI) Correlates of Self-Reported Sleep Quality and Depression Following Mild Traumatic Brain Injury

Abstract: Background: Mild traumatic brain injuries (mTBIs) are a significant social, sport, and military health issue. In spite of advances in the clinical management of these injuries, the underlying pathophysiology is not well-understood. There is a critical need to advance objective biomarkers, allowing the identification and tracking of the long-term evolution of changes resulting from mTBI. Diffusion-weighted imaging (DWI) allows for the assessment of white-matter properties in the brain and shows promise as a sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 108 publications
3
20
0
Order By: Relevance
“…Understanding the structural connectivity alterations of healthy subjects with sleep impairment or patients with sleep disorders are important features in sleep medicine (Raikes et al., 2018; Rostampour et al., 2020). DTI is a method to assess white matter brain integrity and identify microstructural abnormalities.…”
Section: Current Projectsmentioning
confidence: 99%
“…Understanding the structural connectivity alterations of healthy subjects with sleep impairment or patients with sleep disorders are important features in sleep medicine (Raikes et al., 2018; Rostampour et al., 2020). DTI is a method to assess white matter brain integrity and identify microstructural abnormalities.…”
Section: Current Projectsmentioning
confidence: 99%
“…11 Moreover, mTBIs are also commonly associated with mood dysregulation, fatigue, and sleep 2 Journal of Central Nervous System Disease problems, which can impede the recovery process. [12][13][14][15][16][17] One novel and promising approach to overcome these problems is the use of morning blue-wavelength light therapy (ie, at ~480 nm) (BLT). 17,18 Blue light stimulates intrinsically photosensitive retinal ganglion cells (ipRGCs) that project to the suprachiasmatic nucleus (SCN) of the hypothalamus, which serves as the primary regulator of the circadian rhythm.…”
Section: Introductionmentioning
confidence: 99%
“…64 Earlier studies using DTI and DWI have indicated a link between disrupted white matter organization and SWD and fatigue after mTBI, but with small to modest sample sizes and varying time after injury. [65][66][67] Our future work will further investigate longitudinal associations between white matter organization and the development of SWD after mTBI using advanced MRI techniques, including DTI, DWI, and structural morphological measures.…”
Section: Sleep-wake Disturbances and Fatigue After Mtbimentioning
confidence: 99%